Energy Consumption and Economic Growth: Empirical Evidence from MENA Region - Saqib, Najia (International Journal of Energy Economics and Policy, 2021)
This paper examines the causal relationship between energy consumption and real GDP of the fourteen MENA Countries over the period 1987–2019 by using bivariate Vector Auto-regression model and Granger causality approach. This study shows the existence of unidirectional, bidirectional or no causal relationship between energy consumption and economic growth of different countries in MENA Region. The study also suggests the environmental and energy policies should recognize the relationship between energy consumption and economic growth in order to maintain sustainable economic growth in MENA region. Keywords: Energy consumption, Economic growth, Causality, Cointegration, JEL Classifications: C3, O4, Q43 DOI: https://doi.org/10.32479/ijeep.11931